Public willingness to make trade-offs in the development of a hydrogen industry in Australia. (June 2022) - Dumbrell, Nikki P.; Wheeler, Sarah Ann; Zuo, Alec; Adamson, David
Abstract: Hydrogen is attracting increasing attention and investment in the low carbon energy transition. However, it is expected that any transition to hydrogen at a meaningful scale or rate, will be dependent on the industry obtaining a social licence, underpinned by public acceptance. This study analyses responses from a public survey that asked 1, 824 residents of South Australia and Victoria (Australia) to indicate how important six characteristics of a hydrogen industry would be in their decision to support the development of such an industry, namely: (1) safety; (2) climate change mitigation; (3) affordability; (4) reliability; (5) accessibility; and (6) job creation. Overall, safety was rated as the most important characteristic, followed by climate change mitigation and affordability. Fractional multinomial logit model estimates found socio-demographic (e.g. age, location) and attitudinal characteristics (e.g. concern about climate change, hydrogen knowledge) statistically significantly influenced individuals' importance ratings of hydrogen industry characteristics. This research indicates the trade-offs that individuals may—or may not be—willing to make in the transition to hydrogen energy. Such information can be used to align policy and investment decisions with public expectations for the further development of the hydrogen industry in Australia. Highlights: Public preferences were examined to understand priorities for a hydrogen industry to gain acceptance. A survey was used to understand relative importance of six characteristics of a hydrogen industry. Safety was slightly more important than climate change mitigation and affordability. Individuals were more likely to place importance on characteristics that address concerns or provide benefits.